DISTINCTIVE FEATURES ANALYSIS OF FOREIGN LANGUAGE BORROWING WORDS IN JAVANESE LANGUAGE FOUND IN PANJEBAR SEMANGAT MAGAZINE 27th EDITION OF JULY 7, 2018 - Linda Aprillianti (Kajian Linguistik dan Sastra, 2019)
This study is intended to examine the sound change of borrowing word of foreign language in Javanese which is found in Panjebar Semangat magazine. The data is taken from Panjebar Semangat magazine 27th edition on July 7, 2018 and checked using old Javanese dictionary. This study belongs to descriptive qualitative research and used Simak method and Non Participant Observation in collecting the data. The data analysis is done by using Padan method. The result of the study reveals three sound changes of vowels sound and four phonological rules. Then, there are four types of sound change and four phonological rule of consonant sound. The result showed that the sound change of borrowing word in Javanese is influenced by the differences of phonological system between Javanese and the foreign language. Keywords: borrowing word, sound change, distinctive feature, phonology.